Broad-spectrum and full-effect nano foliar fertilizer and preparation method thereof
Patent Information
- Application Number
- CN202611475625.2
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-21
- Publication Date
- 2026-10-27
AI Technical Summary
[0004]针对现有技术的不足,本发明提供了一种广谱全效纳米叶面肥及其制备方法,解决了现有叶面肥在复配多种无机营养元素与有机活性组分时,在偏中性或高浓度盐环境下容易发生金属离子共沉淀,造成养分失效;另外,传统叶面肥液滴在植物叶面的润湿性较差,活性物质难以有效穿透角质层,并且在提升植物光能利用率及抗逆能力方面存在不足的问题
1、本发明通过无水柠檬酸与二价金属离子的前置配位反应,形成稳定的金属-柠檬酸配合物,降低了金属离子的自由水合状态。结合pH动态诱导下的界面重组结构,该体系能够阻断金属离子与磷酸根或氢氧根的结合路径,有效缓解了无机盐在偏中性及高浓度环境下的共沉淀现象,维持了叶面肥在储存与施用过程中的物理稳定性及养分有效性。
Smart Images

Figure CN122977898A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of agricultural fertilizer technology, specifically to a broad-spectrum, all-effect nano-foliar fertilizer and its preparation method. Background Technology
[0002] Foliar fertilization is an agricultural fertilization method that applies nutrients directly to the surface of plant leaves. With the development of modern agricultural technology, the industry currently tends to combine inorganic macro-elements, trace metal ions, and various organic active substances to achieve a more comprehensive fertilizer effect. However, in actual compounding and production processes, it has been found that when high concentrations of divalent metal ions coexist with phosphate and complex organic matter, due to the lack of an effective ion shielding mechanism, the fertilizer system is more prone to co-precipitation reactions of metal salts under near-neutral or high-salinity conditions. This precipitation phenomenon not only disrupts the physical dispersion stability of liquid products, leading to stratification or crusting during storage, but also renders water-soluble nutrients that could be absorbed by plants ineffective.
[0003] Plant leaves are typically covered with a hydrophobic cuticle. Conventional liquid foliar fertilizers have high droplet surface tension, limiting their wetting and spreading on the leaf surface after spraying. Due to this interfacial repulsion, lipid-active components and inorganic nutrients in the solution cannot effectively penetrate the cuticle to enter the leaf tissue, resulting in low actual absorption and utilization rates. Although existing technologies often use conventional chemically synthesized emulsifiers to improve droplet spreading, some synthetic emulsifiers may affect plant cell membrane structure, posing a risk of leaf burn and other phytotoxicity if applied improperly. Furthermore, traditional compound foliar fertilizer formulations often focus on passive nutrient supplementation. Existing preparation processes and formulations still have limitations in areas such as enhancing the effective absorption rate of natural light by leaves and using exogenous active substances to target and activate the crop's endogenous defense signals to improve drought and low-temperature resistance. Summary of the Invention
[0004] To address the shortcomings of existing technologies, this invention provides a broad-spectrum, all-purpose nano-foliar fertilizer and its preparation method. This solves the problems of existing foliar fertilizers, which, when compounded with multiple inorganic nutrients and organic active components, are prone to metal ion co-precipitation in near-neutral or high-concentration salt environments, leading to nutrient inactivation. Furthermore, traditional foliar fertilizer droplets have poor wettability on plant leaves, making it difficult for active substances to effectively penetrate the cuticle, and they are insufficient in improving plant light energy utilization and stress resistance.
[0005] To address the above problems, the present invention provides the following technical solution: In a first aspect, the present invention provides a broad-spectrum, all-effect nano-foliar fertilizer, which adopts the following technical solution: A broad-spectrum, all-purpose nano-foliar fertilizer is prepared from raw materials containing the following proportions: Monk fruit glycoside component A: 400-600 mL; Fatty acid component C: 2.0–5.0 g; Luo Han Guo pomace fluorescent carbon dots B: 150-350 mL; Inorganic nutrient system: 7.0–8.0g; Anhydrous citric acid: 2.26–2.89 g; And replenish to 1000 mL of deionized water; The above raw materials are mixed and the pH of the final product is adjusted to 6.0-7.0 using a pH adjuster. The broad-spectrum, all-effect nano-foliar fertilizer is constructed into a stable nano-multiphase system by multi-component interfacial recombination. Among them, the mogroside component A acts as an amphiphilic skeleton to encapsulate fatty acid component C to form an oil-in-water type colostrum, providing compatibility with plant leaves. Anhydrous citric acid forms a pre-coordination structure with divalent metal ions in the inorganic nutrient system to prevent co-precipitation of inorganic salts in high-salt and near-neutral environments. Under the induction of the pH adjuster, the fluorescent carbon dots B of mogroside pomace cross-link and adsorb at the interface through surface oxygen-containing functional groups and emulsion interface components and coordinated metal ions, providing steric stabilization and light energy conversion function under natural light excitation.
[0006] By employing the above technical solution, the multi-component components of this invention are combined at the microscale to construct a multiphase cross-linked nanosystem. Monk fruit glycoside component A, as a natural triterpenoid saponin, contains hydrophobic saponins and hydrophilic sugar chains in its structure. Under mechanical shearing conditions, these molecules tend to align in a specific direction, utilizing the hydrophobic ends to coat fatty acid component C, thereby constructing a water-in-oil structured nanoscale proemulsion. The hydrophilic sugar chains on the outer layer of this structure exhibit good structural compatibility with the polar components on the surface of plant leaves, helping to reduce the surface tension of the system, expand the spread of droplets on the leaf surface, and thus facilitate the penetration of lipid-active substances into the cuticle.
[0007] To address the issue of inorganic salt coprecipitation, the anhydrous citric acid in the formulation dissociates into carboxyl and hydroxyl groups in aqueous solution, enabling it to coordinate with divalent metal ions in the system. The reaction mechanism is as follows: The formed cyclic metal-citric acid complex largely shields the free hydration state of metal ions, making it difficult for them to combine with phosphate or hydroxide ions in the environment. This helps maintain the dispersion of inorganic salts in environments with rising pH and high salinity, reducing the risk of precipitation.
[0008] With the addition of a pH adjuster, the system environment gradually shifts towards neutrality. At this point, the protonation degree of the oxygen-containing functional groups on the surface of the fluorescent carbon dots B in the monk fruit pomace decreases and they dissociate. The dissociated carbon dots can migrate and adsorb to the interface of the primary emulsion droplets through electrostatic interactions, hydrogen bonding networks, and exchanges with some metal ligands. This multi-component cross-linking constructs a rigid steric hindrance layer around the droplets, which can limit the aggregation of nanodroplets for a relatively long period of time.
[0009] In practical application, carbon dots B adsorbed at the interface absorb short-wavelength spectra from natural light, undergo radiative transitions, and release fluorescence wavelengths suitable for plant absorption. This can, to some extent, supplement the photosynthetically active radiation input of plant leaves. Simultaneously, the released free α-linolenic acid components, after entering leaf tissues, are expected to participate in regulating signal transduction processes such as jasmonic acid within the plant, triggering related defense responses and helping to enhance the plant's physiological adaptability to adverse environments such as drought or low temperatures.
[0010] Preferably, the inorganic nutrient system consists of inorganic salt components containing divalent metal ions and other nutrient components; the inorganic salt components containing divalent metal ions include calcium nitrate tetrahydrate, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, manganese sulfate monohydrate, copper sulfate pentahydrate, and cobalt chloride hexahydrate; the other nutrient components include ammonium nitrate, potassium nitrate, potassium dihydrogen phosphate, potassium iodide, boric acid, and sodium molybdate dihydrate; the ratio of the amount of anhydrous citric acid used to the total molar number of divalent metal ions in the inorganic nutrient system is 1.0:1 to 1.2:1.
[0011] By employing the above technical solution, the molar ratio of anhydrous citric acid to divalent metal ions is controlled within the range of 1.0 to 1.2, allowing the majority of divalent metal ions in the system to participate in coordination reactions. Simultaneously, it prevents osmotic pressure imbalance in the emulsion caused by excessive free citric acid, helping the system maintain relative stability during storage. The combined use of macro- and micro-elements meets the diverse nutrient requirements of crop growth.
[0012] Preferably, the mogroside component A is an extract rich in natural mogrosides obtained by low-temperature water extraction and solid-liquid separation of mogroside pomace; the fluorescent carbon dots B of mogroside pomace is a carbon dot dispersion generated by high-pressure hydrothermal reaction using the solid residue remaining after the above low-temperature water extraction and separation as a carbon source.
[0013] By adopting the above technical solution, this treatment method enables the tiered utilization of by-products from monk fruit processing. The low-temperature water extraction conditions are relatively mild and do not easily damage the surface-active structure of the glycoside molecules; subsequently, the remaining solid material is directly used as a precursor for hydrothermal carbonization, which helps to introduce the original heteroatom structure into the carbon dots, thereby improving its luminescence properties and interfacial affinity.
[0014] Preferably, fatty acid component C is an active component rich in free α-linolenic acid obtained by isothermal enzymatic hydrolysis of perilla seed meal lipids by Candida lipase under nitrogen and antioxidant protection.
[0015] By employing the above-mentioned technical solution, Candida albicans lipase is used for catalytic hydrolysis, causing the release of free α-linolenic acid from the lipids in perilla seed meal. Compared to bound lipids, free α-linolenic acid is more likely to penetrate cell membrane structures and participate in physiological signal transduction, thus helping to stimulate the crop's stress defense response.
[0016] Secondly, this invention provides a method for preparing a broad-spectrum, all-effect nano-foliar fertilizer, employing the following technical solution: A method for preparing a broad-spectrum, all-purpose nano-foliar fertilizer includes the following steps: S1. Solution preparation: Dissolve the inorganic salt component containing divalent metal ions in deionized water separately, add an appropriate amount of anhydrous citric acid, and stir to prepare a divalent metal ion citric acid complex solution; dissolve the remaining nutrient components in deionized water to prepare the remaining nutrient solutions. S2. Preliminary emulsification: Under inert gas protection and heating conditions, fatty acid component C is added dropwise to mogroside component A at a uniform rate, and oil-in-water type primary emulsion is obtained through high shear dispersion emulsification treatment; S3, Interfacial Adsorption Assembly and pH-Induced Recombination: Reduce the stirring speed and pump Luo Han Guo fruit residue fluorescent carbon dots B into the water-in-oil type primary emulsion obtained in S2; then, under continuous stirring, simultaneously add the divalent metal ion citric acid complex solution and pH adjuster prepared in S1, control the pH value of the system to slowly rise to the target endpoint of 6.0 to 7.0 and maintain constant temperature stirring to complete the interfacial structure recombination. S4. Compounding and preparation of final product: Pump the remaining nutrient salt solution obtained in S1 into the system after S3 recombination, mix evenly, cool down, add deionized water to the rated volume, and then discharge to obtain the final product.
[0017] Unlike conventional direct mixing, this method employs a multi-component, stepwise addition approach combined with dynamic adjustment of environmental parameters to construct the system. Metal ions are pre-treated to react with ligands to form complexes, creating an oil-in-water emulsion that serves as the basic template. Subsequently, carbon dots are added while the pH of the system is slowly increased. This dynamic adjustment of the environment gradually alters the charge state at the droplet interface, promoting the orderly migration and anchoring of free components to the interface. This relatively mild physicochemical assembly process helps alleviate localized supersaturation and flocculation problems that easily occur during direct mixing, resulting in a final product with better dispersibility and stability.
[0018] Preferably, in step S2, the operating parameters for the initial emulsification are as follows: nitrogen gas is introduced for protection, and the system temperature is maintained at 40°C to 45°C; the rotation speed of the high-shear dispersing emulsifier is set to 1500 to 2000 rpm; the dripping flow rate of fatty acid component C is 2 to 3 mL / min, and emulsification is continued for 30 to 45 min after the dripping is completed.
[0019] By adopting the above technical solution, the set temperature range and uniform droplet operation combined with a high shear environment help fatty acids to be finely dispersed and coated by the surrounding glycoside molecules, forming relatively uniform primary emulsion droplets; the introduction of nitrogen gas is mainly used to remove oxygen in the reaction system and reduce the oxidation loss of α-linolenic acid during intense shear heating.
[0020] Preferably, in step S3, the pumping flow rate of the fluorescent carbon dots B in the monk fruit pomace is 5 to 10 mL / min; the pH adjuster is a 10 wt% to 12 wt% aqueous solution of potassium hydroxide; the dropping rate of the pH adjuster is controlled so that the pH value of the system rises slowly at an average rate of 0.1 to 0.15 pH units / min until the target endpoint of pH value of 6.0 to 7.0 is reached, and the system is stirred at a constant temperature for 30 to 45 min under this pH condition.
[0021] By employing the above technical solution, the rate of pH increase is limited, making the deprotonation transition of functional groups on the carbon dot surface relatively gradual. This allows time for the orderly migration of carbon dot particles to the emulsion interface, preventing disordered aggregation. Combined with a certain period of isothermal stirring, non-covalent interactions between the components are established, thereby maintaining the overall morphology of the multiphase structure.
[0022] Preferably, in step S2, the mogroside component A is prepared by the following pretreatment steps: the mogroside pomace is mixed with deionized water at a mass ratio of 1:10 to 1:15, the extraction temperature is controlled at 50℃ to 60℃, the extraction time is 2.0h to 3.0h, the solid-liquid separation is performed by filtering through a 200-mesh filter, and the extracted liquid is collected as mogroside component A. The solid residue obtained by separation is reserved for later use.
[0023] By employing the above-mentioned technical solution, controlling a lower extraction temperature and a suitable water-to-material ratio, the aim is to dissolve the residual glycosides in the fruit pomace while reducing the excessive release of large-molecule polysaccharides. This extraction strategy can control the overall viscosity of the liquid, reducing physical resistance for subsequent shear emulsification operations.
[0024] Preferably, in step S3, the fluorescent carbon dots B from the monk fruit pomace are prepared by the following pretreatment steps: the separated solid residue is placed in a high-pressure hydrothermal reactor, deionized water is added to control the solid-liquid mass ratio to be 1:5 to 1:10, the hydrothermal reaction temperature is set to 180℃ to 220℃, and the reaction is maintained for 8 to 10 hours; after naturally cooling to room temperature, the insoluble solids are filtered out, and the obtained filtrate is the fluorescent carbon dots B from the monk fruit pomace.
[0025] By employing the above technical solution, the high-pressure hydrothermal environment induces the hydrolysis, polymerization, and partial carbonization of carbohydrates such as cellulose within the residue, transforming them into nanoscale carbon dot structures. This reaction process retains some oxygen-containing groups on the product surface, satisfying the reaction conditions for subsequent interfacial cross-linking, without the need for the introduction of additional exogenous surface modifiers.
[0026] Preferably, in step S2, fatty acid component C is prepared by the following pretreatment steps: lipids extracted and recovered from perilla seed meal are mixed with deionized water at a mass ratio of 1:3 to 1:5, Candida lipase is added, and enzymatic hydrolysis is carried out at a constant temperature of 40°C to 45°C for 2.0 h to 4.0 h; nitrogen gas is continuously introduced during the enzymatic hydrolysis, and D-α-tocopherol is added at 0.1 wt% to 0.3 wt% of the lipid mass; after the enzymatic hydrolysis is completed, the temperature is raised to 85°C to inactivate the enzyme, and the upper lipid phase is collected by centrifugation, which is fatty acid component C.
[0027] By employing the above-mentioned technical solution, Candida albicans lipase is used to catalyze the cleavage of triglyceride backbones in lipids to obtain target fatty acids. Considering the instability of carbon-carbon double bonds in the product, an inert gas is introduced and D-α-tocopherol is added to create a synergistic antioxidant environment, which can alleviate lipid peroxidation degradation during the long and time-consuming enzymatic hydrolysis process.
[0028] This invention provides a broad-spectrum, all-purpose nano-foliar fertilizer and its preparation method. It possesses the following beneficial effects: 1. This invention utilizes the pre-coordination reaction between anhydrous citric acid and divalent metal ions to form a stable metal-citric acid complex, thereby reducing the free hydration state of the metal ions. Combined with the interfacial reorganization structure induced by pH dynamics, this system can block the binding pathway between metal ions and phosphate or hydroxide ions, effectively alleviating the co-precipitation phenomenon of inorganic salts under near-neutral and high-concentration environments, and maintaining the physical stability and nutrient availability of foliar fertilizers during storage and application.
[0029] 2. This invention utilizes mogrosides as an amphiphilic backbone to encapsulate free α-linolenic acid, constructing an oil-in-water nanoemulsion. The hydrophilic sugar chains on the periphery of this emulsion structure are structurally compatible with the polar components of plant leaves, reducing droplet surface tension and increasing the spreading area on the leaf surface. This nanoscale dispersion reduces the physical resistance to the entry of active lipids into the leaf, facilitating the penetration of free α-linolenic acid into the cuticle, thereby helping to trigger the plant's physiological defense response and improving the crop's environmental adaptability.
[0030] 3. This invention introduces fluorescent carbon dots from monk fruit pomace during the emulsion interface assembly process. The carbon dots adsorbed at the interface provide steric hindrance through multi-component cross-linking, limiting the aggregation of droplets. Simultaneously, the carbon dot material attached to the leaf surface can absorb short-wavelength spectra from ambient natural light and undergo radiative transitions, releasing fluorescence wavelengths suitable for chlorophyll absorption. This moderately supplements the photosynthetically active radiation received by the leaves, thus providing a certain auxiliary promoting effect on improving the photosynthetic efficiency of crops. Attached Figure Description
[0031] Figure 1 The diagram shows the main spectral characteristics of each component and the composite system at different preparation stages; where: (a) is a schematic diagram reflecting the distribution of infrared absorption peak positions, and (b) is a schematic diagram showing the distribution of ultraviolet characteristic absorption wavelengths; Figure 2 The diagrams show the particle size and fluorescence characteristics of the composite system at different preparation stages; (a) shows the average hydrodynamic particle size and polydispersity index, and (b) shows the corresponding maximum fluorescence emission wavelength. Figure 3 The changes in average hydrodynamic particle size and turbidity of the system during storage are shown; where: (a) is a schematic diagram of the particle size change trend over time, and (b) is a schematic diagram of the turbidity change trend of the corresponding sample. Figure 4 The graph shows the changes in α-linolenic acid retention rate and peroxide value in the system under accelerated oxidation conditions; where: (a) shows the change in retention rate over time, and (b) shows the corresponding change in peroxide value. Figure 5 The following are the trends of physiological indicators of leaves of monk fruit seedlings after foliar spraying treatment over time; among them: (a) a schematic diagram of relative electrolyte leakage rate, and (b) a schematic diagram reflecting the change of SPAD value. Figure 6 The diagram shows the diurnal variation characteristics of photosynthetic parameters of Luo Han Guo leaves after spraying treatment; where: (a) is a schematic diagram of the difference in net photosynthetic rate, and (b) is a schematic diagram of the corresponding change in stomatal conductance. Figure 7The curves show the time-dependent changes in the activity of defense-related enzymes in the leaves of Luo Han Guo after spraying; among them: (a) is a schematic diagram showing the changes in peroxidase (POD) activity, and (b) is a schematic diagram showing the changes in phenylalanine ammonia-lyase (PAL) activity. Figure 8 This is a flowchart of a method for preparing a broad-spectrum, all-effect nano-foliar fertilizer according to the present invention. Detailed Implementation
[0032] The technical solutions of the embodiments of the present invention will be clearly and completely described below with reference to the accompanying drawings. Obviously, the described embodiments are only some embodiments of the present invention, and not all embodiments. Based on the embodiments of the present invention, all other embodiments obtained by those skilled in the art without creative effort are within the scope of protection of the present invention.
[0033] The main raw materials and reagents used in the following examples and comparative examples have the following sources and specifications. Reagents not specifically mentioned are all commercially available analytical grade or higher grade products.
[0034] Monk fruit residue is obtained by hot air drying of the residue after extracting juice from fresh monk fruit with pure water. The moisture content is less than 8 wt%. It is then physically crushed and passed through a 120-mesh sieve for later use.
[0035] Perilla seed meal is a solid cake obtained by cold pressing perilla seeds to extract some of the oil. The residual oil content is 12wt% to 15wt%. It is physically crushed and passed through an 80-mesh sieve for later use.
[0036] Candida lipase, CAS number 9001-62-1, is a solid powder with a nominal enzyme activity of 700 U / mg.
[0037] The CAS number for D-α-tocopherol is 59-02-9, and its purity is ≥95%.
[0038] The CAS number for the mogroside V standard is 88901-36-4, with a purity of ≥98%, and it is used as a standard reference for quantitative detection.
[0039] The α-linolenic acid standard has the CAS number 463-40-1 and a purity of ≥99%, and is used as a standard reference substance for quantitative detection.
[0040] The monomeric inorganic salts constituting the plant inorganic nutrient system include ammonium nitrate, potassium nitrate, calcium nitrate tetrahydrate, magnesium sulfate heptahydrate, potassium dihydrogen phosphate, potassium iodide, boric acid, manganese sulfate monohydrate, zinc sulfate heptahydrate, sodium molybdate dihydrate, copper sulfate pentahydrate, and cobalt chloride hexahydrate. The above-mentioned inorganic salts, as well as the anhydrous citric acid used to prepare the buffer solution and the potassium hydroxide used to adjust the pH, are all conventional commercially available analytical grade products, and their chemical structures and physical properties are well known to those skilled in the art.
[0041] Preparation Example 1: This preparation example provides a method for preparing mogroside component A, including the following steps: (1) Low-temperature water extraction: The pomace of monk fruit was treated by low-temperature water extraction, with the extraction temperature controlled at 50℃ to 60℃ and the extraction time at 2.0h to 3.0h, and the solid-liquid mass ratio of monk fruit pomace to deionized water controlled at 1:10 to 1:15. In this preparation example, the extraction temperature was 55℃, the extraction time was 2.5h, and the solid-liquid mass ratio of monk fruit pomace to deionized water was 1:12.
[0042] (2) Solid-liquid separation: After extraction, the solid-liquid mixture is filtered using a 200-mesh filter to achieve solid-liquid separation and obtain an extract rich in mogrosides. The obtained extract is denoted as mogroside component A. The separated solid residue is used as the carbon source for preparing fluorescent carbon dots of mogroside pomace in Preparation Example 2.
[0043] (3) Index detection: The content of mogroside V, total mogroside content and solid content in mogroside component A were detected.
[0044] Preparation Example 2: This preparation example provides a method for preparing fluorescent carbon dots B from monk fruit pomace, including the following steps: (1) Hydrothermal treatment: The pomace of Luo Han Guo obtained after glycoside extraction in Preparation Example 1 was added to a high-pressure hydrothermal reactor as a carbon source, and deionized water was added to control the solid-liquid mass ratio at 1:5 to 1:10. Hydrothermal treatment was carried out at a temperature of 180℃ to 220℃ and a holding time of 8h to 10h. In this preparation example, a solid-liquid mass ratio of 1:8, a hydrothermal reaction temperature of 200℃, and a holding time of 9h were specifically used.
[0045] (2) Separation and purification: After the hydrothermal reaction is completed, the reaction system is naturally cooled to room temperature, and the insoluble solids are filtered out by a filter press to obtain the fluorescent carbon dot dispersion of Luo Han Guo pomace. The obtained Luo Han Guo pomace fluorescent carbon dot is recorded as Luo Han Guo pomace fluorescent carbon dot B.
[0046] (3) Performance testing: The average hydrodynamic particle size, polydispersity index (PDI), zeta potential, fluorescence excitation spectrum characteristics, and fluorescence emission spectrum characteristics of the fluorescent carbon dots B obtained from the Luo Han Guo pomace were tested. The average hydrodynamic particle size of the fluorescent carbon dots B from the Luo Han Guo pomace was 3.6 nm, the polydispersity index (PDI) was 0.128, the zeta potential was -22.4 mV, the maximum excitation wavelength was 365 nm, and the maximum emission wavelength was 448 nm. For specific test results, please refer to Test Example 2.
[0047] Preparation Example 3: This preparation example provides a method for preparing fatty acid component C rich in free α-linolenic acid, including the following steps: (1) Enzymatic hydrolysis: The lipids recovered from perilla seed meal were mixed with deionized water at a mass ratio of 1:3 to 1:5, and Candida lipase was added. The mixture was enzymatically hydrolyzed at a constant temperature of 40°C to 45°C for 2.0 h to 4.0 h. Nitrogen gas was continuously introduced for protection during the enzymatic hydrolysis process, and D-α-tocopherol was added at 0.1 wt% to 0.3 wt% of the lipid mass for antioxidant protection.
[0048] (2) Enzyme inactivation and separation: After the enzymatic hydrolysis, the system was heated to 85°C for enzyme inactivation treatment, then centrifuged and the upper lipid phase was collected to obtain fatty acid component C rich in free α-linolenic acid.
[0049] (3) Index detection: The content of free fatty acids, α-linolenic acid, the proportion of α-linolenic acid in total fatty acids, and peroxide value in fatty acid component C were detected.
[0050] Example 1: Please see Figure 8 This embodiment provides a method for preparing a broad-spectrum, all-purpose nano-foliar fertilizer, including the following steps: (1) Preparation of divalent metal ion citric acid complex solution and other nutrient salt solutions: Weigh out 7.5g of each nutrient component constituting the inorganic nutrient salt system, including 1.500g of ammonium nitrate, 1.800g of potassium nitrate, 1.600g of calcium nitrate tetrahydrate, 1.200g of magnesium sulfate heptahydrate, 1.350g of potassium dihydrogen phosphate, 0.005g of potassium iodide, 0.020g of boric acid, 0.012g of manganese sulfate monohydrate, 0.008g of zinc sulfate heptahydrate, 0.003g of sodium molybdate dihydrate, 0.001g of copper sulfate pentahydrate and 0.001g of cobalt chloride hexahydrate. The total mass of the above nutrient components is 7.500g. The inorganic salts containing divalent metal ions, including calcium nitrate tetrahydrate, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, manganese sulfate monohydrate, copper sulfate pentahydrate, and cobalt chloride hexahydrate, were weighed separately and dissolved together in 50 mL of deionized water. Anhydrous citric acid was added at a ratio of 1.1:1 (approximately 2.48 g of anhydrous citric acid). The mixture was stirred at room temperature for 30 min to obtain a citric acid complex solution containing divalent metal ions. The remaining ammonium nitrate, potassium nitrate, potassium dihydrogen phosphate, potassium iodide, boric acid, and sodium molybdate dihydrate were dissolved in 150 mL of deionized water to obtain the remaining nutrient salt solution.
[0051] (2) Preliminary emulsification under nitrogen protection: 500 mL of mogroside component A prepared according to the method of Preparation Example 1 was pumped into a reactor equipped with a high-shear dispersion emulsifier. Nitrogen was introduced for protection, and the water bath temperature was raised and maintained at 45°C. The high-shear dispersion emulsifier was started and the speed was set to 1800 rpm. 3.5 g of fatty acid component C prepared according to the method of Preparation Example 3 was added dropwise into the reactor at a flow rate of 3 mL / min. After the addition was completed, high-shear dispersion emulsification was continued for 40 min, so that fatty acid component C formed an emulsion dispersion state under the action of mogroside component A, and an oil-in-water type primary emulsion was obtained.
[0052] (3) Interfacial adsorption assembly and pH-induced interfacial reorganization: Reduce the stirring speed to 400 rpm, and slowly pump 250 mL of the Luo Han Guo fruit residue fluorescent carbon dot B prepared according to the method of Preparation Example 2 into the water-in-oil type primary emulsion at a flow rate of 10 mL / min. Do not adjust the pH of the system during the pumping process. At this time, the pH of the system is about 4.5. After the pumping is completed, start the synchronous dripping system. While adding the divalent metal ion citric acid complex solution prepared in step (1) at a flow rate of 5 mL / min, add the potassium hydroxide aqueous solution with a mass fraction of 12 wt% simultaneously. Use an online pH meter to control the dripping rate of the potassium hydroxide aqueous solution so that the pH value of the liquid phase in the reactor rises slowly at an average rate of about 0.15 pH units / min until it reaches and is maintained at 6.8. Continue to stir at a constant temperature for 40 min under the condition of pH 6.8 to promote the interaction between the oxygen-containing functional groups on the surface of Luo Han Guo fruit residue fluorescent carbon dot B, the emulsion interface components and metal ions, and promote the reorganization of the interfacial structure.
[0053] (4) Inorganic nutrient salt compounding and final product preparation: After the interface recombination process is completed, the remaining nutrient salt solution prepared in step (1) is pumped into the reactor at a flow rate of 5 mL / min. Stirring is continued for 20 min until the system is mixed evenly. Heating is stopped and the temperature is lowered to room temperature. Deionized water is added to a total volume of 1000 mL. Nitrogen protection is removed, and the product is filtered out to obtain a composite nano-leaf fertilizer with a uniform appearance and no obvious layering.
[0054] Example 2: This embodiment provides a method for preparing a broad-spectrum, all-purpose nano-foliar fertilizer, including the following steps: (1) Preparation of divalent metal ion citric acid complex solution and other nutrient salt solutions: Weigh 8.0g of each nutrient component constituting the inorganic nutrient salt system. The mass ratio between each nutrient component is the same as in Example 1. Among them, ammonium nitrate 1.600g, potassium nitrate 1.920g, calcium nitrate tetrahydrate 1.7067g, magnesium sulfate heptahydrate 1.280g, potassium dihydrogen phosphate 1.440g, potassium iodide 0.0053g, boric acid 0.0213g, manganese sulfate monohydrate 0.0128g, zinc sulfate heptahydrate 0.0085g, sodium molybdate dihydrate 0.0032g, copper sulfate pentahydrate 0.0011g, and cobalt chloride hexahydrate 0.0011g. The total mass of the above nutrient components is 8.000g. The inorganic salts containing divalent metal ions, including calcium nitrate tetrahydrate, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, manganese sulfate monohydrate, copper sulfate pentahydrate, and cobalt chloride hexahydrate, were weighed separately and dissolved together in 50 mL of deionized water. Anhydrous citric acid was added at a ratio of 1.2:1 to the total molar amount of divalent metal ions, with approximately 2.89 g of anhydrous citric acid added. The mixture was stirred at room temperature for 30 min to obtain a citric acid complex solution containing divalent metal ions. The remaining ammonium nitrate, potassium nitrate, potassium dihydrogen phosphate, potassium iodide, boric acid, and sodium molybdate dihydrate were dissolved in 150 mL of deionized water to obtain the remaining nutrient salt solution.
[0055] (2) Preliminary emulsification under nitrogen protection: 400 mL of mogroside component A prepared according to the method of Preparation Example 1 was pumped into a reactor equipped with a high-shear dispersion emulsifier. Nitrogen was introduced for protection, and the system temperature was maintained at 40°C. The high-shear dispersion emulsifier was started and the speed was set to 1500 rpm. 5.0 g of fatty acid component C prepared according to the method of Preparation Example 3 was added dropwise to the reactor at a flow rate of 2 mL / min. After the addition was completed, high-shear dispersion emulsification was continued for 45 min, so that fatty acid component C formed an emulsion dispersion state under the action of mogroside component A, and an oil-in-water type primary emulsion was obtained.
[0056] (3) Interfacial adsorption assembly and pH-induced interfacial reorganization: Reduce the stirring speed to 300 rpm, and slowly pump 350 mL of the Luo Han Guo fruit residue fluorescent carbon dot B prepared according to the method of Preparation Example 2 into the water-in-oil type primary emulsion at a flow rate of 5 mL / min; after the pumping is completed, simultaneously add the divalent metal ion citric acid complex solution prepared in step (1) and a potassium hydroxide aqueous solution with a mass fraction of 10 wt%, and control the dropping rate of the potassium hydroxide aqueous solution so that the pH value of the system slowly rises at an average rate of about 0.1 pH units / min until it reaches and is maintained at 7.0. Continue to stir at a constant temperature for 45 min under the condition of pH 7.0 to promote the interaction between the oxygen-containing functional groups on the surface of Luo Han Guo fruit residue fluorescent carbon dot B, the emulsion interface components and metal ions, and promote the reorganization of the interfacial structure.
[0057] (4) Inorganic nutrient salt compounding and final product preparation: After the interface recombination process is completed, the remaining nutrient salt solution prepared in step (1) is slowly pumped into the reactor, and the mixture is stirred for 15 minutes until the system is evenly mixed. The temperature is lowered to room temperature, and deionized water is added to a total volume of 1000 mL. The composite nano foliar fertilizer is then discharged.
[0058] Example 3: This embodiment provides a method for preparing a broad-spectrum, all-purpose nano-foliar fertilizer, including the following steps: (1) Preparation of divalent metal ion citric acid complex solution and other nutrient salt solutions: Weigh 7.5g of each nutrient component constituting the inorganic nutrient salt system. The types and amounts of each nutrient component are the same as in Example 1. Dissolve the inorganic salt containing divalent metal ions separately in 50mL of deionized water. Add anhydrous citric acid at a ratio of 1.1:1 (citric acid to total molar number of divalent metal ions). The amount of anhydrous citric acid added is approximately 2.48g. Stir at room temperature for 30min to obtain divalent metal ion citric acid complex solution. Dissolve the remaining nutrient components in 150mL of deionized water to obtain the other nutrient salt solutions.
[0059] (2) Preliminary emulsification under nitrogen protection: The operation of step (2) in Example 1 was carried out. 500 mL of mogroside component A and 3.5 g of fatty acid component C were used for preliminary emulsification to obtain an oil-in-water type colostrum.
[0060] (3) Interfacial adsorption assembly and pH-induced interfacial recombination: The stirring speed was reduced to 400 rpm, and 250 mL of Luo Han Guo fruit residue fluorescent carbon point B was pumped in. Then, the divalent metal ion citric acid complex solution prepared in step (1) and a potassium hydroxide aqueous solution with a mass fraction of 12 wt% were added dropwise. The addition of potassium hydroxide aqueous solution was controlled by an online pH meter to make the pH value of the system rise slowly and maintain at 6.0. The system was stirred at a constant temperature for 40 min to investigate the changes in the interfacial assembly state and stability of the system under a lower pH endpoint.
[0061] (4) Inorganic nutrient salt compounding and final product preparation: Pump in the remaining nutrient salt solution prepared in step (1), stir for 20 min until the system is evenly mixed, cool down and add deionized water to the total volume of 1000 mL, and discharge to obtain composite nano foliar fertilizer.
[0062] Example 4: This embodiment provides a method for preparing a composite nano-foliar fertilizer, including the following steps: (1) Preparation of divalent metal ion citric acid complex solution and other nutrient salt solutions: Weigh 7.5g of each nutrient component constituting the inorganic nutrient salt system. The types and amounts of each nutrient component are the same as in Example 1. Dissolve the inorganic salt containing divalent metal ions separately in 50mL of deionized water. Add anhydrous citric acid at a ratio of 1.0:1 to the total molar number of divalent metal ions. The amount of anhydrous citric acid added is about 2.26g. Stir at room temperature for 30min to obtain divalent metal ion citric acid complex solution. Dissolve the remaining nutrient components in 150mL of deionized water to obtain the other nutrient salt solutions.
[0063] (2) Preliminary emulsification under nitrogen protection: The operation of step (2) in Example 1 was carried out. 500 mL of mogroside component A and 3.5 g of fatty acid component C were used for preliminary emulsification to obtain an oil-in-water type colostrum.
[0064] (3) Interfacial adsorption assembly and pH-induced interfacial recombination: Follow the operation of step (3) in Example 1, pump in 250 mL of Luo Han Guo fruit residue fluorescent carbon point B, and simultaneously add the divalent metal ion citric acid complex solution and potassium hydroxide aqueous solution prepared in step (1) to slowly raise the pH value of the system to 6.8 and maintain it at 6.8, and continue to stir at a constant temperature for 40 min.
[0065] (4) Inorganic nutrient salt compounding and final product preparation: Pump in the remaining nutrient salt solution prepared in step (1), stir for 20 min until the system is evenly mixed, cool down and add deionized water to the total volume of 1000 mL, and discharge to obtain composite nano foliar fertilizer.
[0066] Example 5: This embodiment provides a method for preparing a composite nano-foliar fertilizer, including the following steps: (1) Preparation of citric acid complex solution for divalent metal ions and other nutrient solutions: Weigh 7.5g of each nutrient component constituting the inorganic nutrient system. The types and amounts of each nutrient component are the same as in Example 1. Dissolve the inorganic salt containing divalent metal ions separately in 50mL of deionized water. Add anhydrous citric acid at a ratio of 1.1:1 (citric acid to total molar number of divalent metal ions). The amount of anhydrous citric acid added is approximately 2.48g, to obtain the citric acid complex solution for divalent metal ions. Dissolve the remaining nutrient components in 150mL of deionized water to obtain the other nutrient solutions.
[0067] (2) Preliminary emulsification under nitrogen protection: 600 mL of mogroside component A prepared according to the method of Preparation Example 1 was pumped into the reactor. The system temperature was maintained at 45°C and nitrogen was introduced for protection. The high shear dispersion emulsifier was turned on and the speed was set to 2000 rpm. 2.0 g of fatty acid component C prepared according to the method of Preparation Example 3 was slowly added dropwise to the reactor. After the addition was completed, high shear dispersion emulsification was continued for 30 min so that fatty acid component C formed an emulsion dispersion state under the action of mogroside component A, and an oil-in-water type primary emulsion was obtained.
[0068] (3) Interfacial adsorption assembly and pH-induced interfacial recombination: Reduce the stirring speed to 500 rpm, pump in 150 mL of Luo Han Guo fruit residue fluorescent carbon point B, and then simultaneously add the divalent metal ion citric acid complex solution prepared in step (1) and a potassium hydroxide aqueous solution with a mass fraction of 12 wt% to make the pH value of the system slowly rise and maintain at 6.8, and continue to stir at a constant temperature for 30 min.
[0069] (4) Inorganic nutrient salt compounding and final product preparation: Pump in the remaining nutrient salt solution prepared in step (1), stir for 20 min until the system is evenly mixed, cool down and add deionized water to the total volume of 1000 mL, and discharge to obtain composite nano foliar fertilizer.
[0070] Example 6: This embodiment provides a method for preparing a composite nano-foliar fertilizer, including the following steps: (1) Preparation of divalent metal ion citric acid complex solution and other nutrient salt solutions: Weigh 7.0g of each nutrient component constituting the inorganic nutrient salt system. The mass ratio between each nutrient component is the same as in Example 1. Among them, ammonium nitrate 1.400g, potassium nitrate 1.680g, calcium nitrate tetrahydrate 1.4933g, magnesium sulfate heptahydrate 1.120g, potassium dihydrogen phosphate 1.260g, potassium iodide 0.0047g, boric acid 0.0187g, manganese sulfate monohydrate 0.0112g, zinc sulfate heptahydrate 0.0075g, sodium molybdate dihydrate 0.0028g, copper sulfate pentahydrate 0.0009g, and cobalt chloride hexahydrate 0.0009g. The total mass of the above nutrient components is 7.000g. The inorganic salts containing divalent metal ions were dissolved separately in 50 mL of deionized water. Anhydrous citric acid was added at a ratio of 1.1:1 to the total molar amount of divalent metal ions, with an amount of approximately 2.32 g of anhydrous citric acid added, to obtain a divalent metal ion citric acid complex solution. The remaining nutrient components were dissolved in 150 mL of deionized water to obtain the remaining nutrient salt solution.
[0071] (2) Preliminary emulsification under nitrogen protection: The operation of step (2) in Example 1 was carried out. 500 mL of mogroside component A and 3.5 g of fatty acid component C were used for preliminary emulsification to obtain an oil-in-water type colostrum.
[0072] (3) Interfacial adsorption assembly and pH-induced interfacial recombination: Reduce the stirring speed to 400 rpm, pump in 250 mL of Luo Han Guo fruit residue fluorescent carbon point B, and simultaneously add the divalent metal ion citric acid complex solution and potassium hydroxide aqueous solution prepared in step (1) to slowly raise the pH value of the system to 6.5 and maintain it at 6.5. Continue to stir at a constant temperature for 40 min.
[0073] (4) Inorganic nutrient salt compounding and final product preparation: Pump in the remaining nutrient salt solution prepared in step (1), stir for 20 min until the system is evenly mixed, cool down and add deionized water to the total volume of 1000 mL, and discharge to obtain composite nano foliar fertilizer.
[0074] Comparative Example 1: Compared with Example 1, the difference is that the glycoside component A prepared according to the method of Preparation Example 1 is not added, and an equal volume of deionized water is used to replace it for high-shear emulsification treatment; otherwise, they are the same.
[0075] Comparative Example 2: Compared with Example 1, the difference is that the Luo Han Guo residue fluorescent carbon dots B prepared according to the method of Preparation Example 2 are not added, and are replaced with an equal volume of deionized water; otherwise, they are the same.
[0076] Comparative Example 3: Compared with Example 1, the difference is that the active fatty acid component C prepared according to the method of Preparation Example 3 is not added, otherwise they are the same.
[0077] Comparative Example 4: Compared with Example 1, the difference is that anhydrous citric acid is not added in step 1, and divalent metal cations are not separated. Instead, all the monomeric inorganic salts that constitute the plant inorganic nutrient system are directly dissolved in 200 mL of deionized water to prepare a mixed salt solution, which is added all at once in step 4. The rest are the same.
[0078] Comparative Example 5: Compared with Example 1, the difference is that the enzymatic hydrolysis process in Preparation Example 3 and the primary emulsification process in Example 1 both eliminated the nitrogen protection environment, and D-α-tocopherol was not added in Preparation Example 3, but all other aspects were the same.
[0079] Comparative Example 6: Compared with Example 1, the difference is that the staged high-shear emulsification, isoelectric point co-adsorption and pH-responsive induced interfacial cross-linking steps are cancelled. Instead, the glycoside component A, the fluorescent carbon dots of monk fruit residue B, the active fatty acid component C, the coordination buffer and the main nutrient salt retention solution are directly mixed and stirred at one time. All other steps are the same.
[0080] Comparative Example 7: Compared with Example 1, the difference is that the glycoside component A prepared according to the method of Preparation Example 1 was replaced with an aqueous solution of Tween-80 conventional chemical surfactant with an equal volume mass fraction of 1 wt%, otherwise the same.
[0081] Test Example 1: This test case uses Fourier transform infrared spectroscopy and ultraviolet-visible absorption spectroscopy to characterize each component and the sample at different stages of the assembly process, in order to analyze the changes in the functional group vibration characteristics and ultraviolet absorption characteristics before and after the components are compounded, and to evaluate the possibility of interfacial interactions between the components.
[0082] (1) Sample preparation: The following samples were prepared: the mogroside A obtained in Preparation Example 1, the fluorescent carbon dots of mogroside pomace obtained in Preparation Example 2, the oil-in-water type colostrum obtained in step (2) of Example 1, and the composite nano-foliar fertilizer obtained in Example 1. They were pre-frozen at -80°C for 12 hours, and then transferred to a vacuum freeze dryer for 48 hours. After grinding, the corresponding solid powder samples were obtained. The fatty acid component C obtained in Preparation Example 3 was also prepared for later use.
[0083] (2) Fourier transform infrared spectroscopy test: Weigh 1 mg of the above solid powder sample and grind and mix it thoroughly with 100 mg of dry potassium bromide powder in an agate mortar. Press the mixture into a transparent sheet under a pressure of 10 MPa. For the liquid fatty acid component C, the potassium bromide salt window coating method is used for sample preparation.
[0084] The prepared samples were placed in a Fourier transform infrared spectrometer at 4000 cm⁻¹. -1 Up to 400cm -1 The scan was performed within the specified wavenumber range, with a resolution set to 4 cm⁻¹. -1 The infrared transmission spectra of each sample were obtained by performing 32 cumulative scans, and the positions of the main characteristic peaks in the hydroxyl stretching vibration region and the carbonyl stretching vibration region were recorded.
[0085] (3) Ultraviolet-Visible Absorption Spectroscopy Test: The following components were taken separately: unfrozen monk fruit glycoside component A, monk fruit pomace fluorescent carbon dots B, oil-in-water type colostrum, and the composite nano foliar fertilizer prepared in Example 1. They were diluted 500 times with deionized water; fatty acid component C was diluted 500 times with anhydrous ethanol.
[0086] Take an appropriate amount of the above diluent and add it to a 1cm quartz cuvette. Use the corresponding pure solvent as a blank reference and perform continuous scanning in the wavelength range of 200nm to 700nm. Record the UV-Vis absorption spectrum and main characteristic absorption wavelength of each sample.
[0087] The main spectral characteristic parameters obtained are shown in Table 1.
[0088] Table 1. Positions of the main infrared absorption peaks and characteristic ultraviolet absorption wavelengths of the composite nano-dispersion system and its components:
[0089] According to Table 1 and Figure 1 The results show that the mogroside A, fatty acid C, and fluorescent carbon dots B from the mogroside pomace exhibit different infrared absorption peaks and ultraviolet absorption characteristics.
[0090] In Example 1, the hydroxyl stretching vibration peak of the water-in-oil colostrum was located at 3371.6 cm⁻¹. -1 The 3385.4 cm of mogroside component A -1 Compared to a shift towards lower wavenumbers, its carbonyl stretching vibration peak is located at 1741.2 cm⁻¹. -1 The absorption region is close to the carbonyl characteristic absorption region of fatty acid component C. Simultaneously, the oil-in-water type colostrum exhibits characteristic UV absorption near 216.8 nm and 238.2 nm. These spectral changes indicate that after preliminary emulsification, the local chemical environment of mogroside component A and fatty acid component C underwent certain changes, consistent with possible hydrogen bonding and hydrophobic interactions between the two components.
[0091] After further addition of Luo Han Guo fruit pomace fluorescent carbon point B and completion of pH adjustment and inorganic nutrient salt compounding, the hydroxyl stretching vibration peak of the final product in Example 1 shifted further to 3352.1 cm⁻¹. -1 The carbonyl stretching vibration peak is located at 1728.9 cm⁻¹. -1 Meanwhile, its ultraviolet characteristic absorption wavelengths are located at 224.3 nm and 283.6 nm, with the absorption characteristics at the longer wavelengths shifting to some extent relative to the 278.4 nm of the fluorescent carbon point B in the pomace of Luo Han Guo.
[0092] The changes in the positions of the infrared absorption peaks and the ultraviolet absorption characteristics indicate that the local chemical environment of each component changed during the formation of the composite system. Combined with the characteristics of the oxygen-containing functional groups on the surface of the fluorescent carbon dots B in the Luo Han Guo pomace and the presence of divalent metal ions in the system, the observed spectral changes are consistent with the involvement of oxygen-containing functional groups in interfacial interactions and metal ion coordination, providing spectroscopic support for the participation of various non-covalent interactions in the interfacial assembly of composite nanodispersion systems.
[0093] Test Example 2: This test case analyzes the influence of the staged assembly process on the dispersion state of the system and the fluorescence characteristics of the fluorescent carbon dots B in the pomace of Luo Han Guo by measuring the average hydrodynamic particle size, polydispersity index (PDI), zeta potential and fluorescence spectral characteristics of samples at different stages of the staged assembly process.
[0094] (1) Sample preparation: Five mL each of the oil-in-water emulsion obtained in step (2) of Example 1, the interfacial reconstituted emulsion obtained in step (3), and the final product obtained in step (4) were taken as test samples. Simultaneously, fluorescent carbon dots B from the pomace of *Siraitia grosvenorii* obtained in Preparation Example 2 were taken as reference samples. Each liquid sample was diluted 100 times with deionized water to reduce the influence of multiple light scattering on the test results. Then, the samples were transferred to an ultrasonic cleaner and ultrasonically degassed for 5 minutes at room temperature for later use.
[0095] (2) Measurement of average hydrodynamic particle size, polydispersity index and Zeta potential: Take an appropriate amount of the above-treated diluted solution and transfer it into a dedicated polystyrene sample cell, which is then placed in the sample chamber of a dynamic light scattering instrument. Set the test temperature to 25°C, and after equilibration for 120 seconds, perform the measurement at a backscattering angle of 173°. Repeat the measurement three times for each sample, and record the average hydrodynamic particle size and polydispersity index (PDI). Subsequently, transfer the sample into a folded capillary electrode cell, and determine the zeta potential of the sample using mixed-mode phase analysis light scattering technology.
[0096] (3) Fluorescence spectroscopy test: The diluted solution after the above treatment was transferred into a four-sided transparent quartz cuvette and placed in a fluorescence spectrophotometer. A pre-scan was performed in the range of excitation wavelength from 360 nm to 370 nm. After determining the maximum excitation wavelength, the excitation slit and emission slit were both set to 5 nm. A scan was performed in the wavelength range of 400 nm to 650 nm to obtain the steady-state fluorescence emission spectrum of the sample and the maximum emission wavelength was recorded.
[0097] The average hydrodynamic particle size, polydispersity index, zeta potential, and fluorescence spectral characteristics of each sample are shown in Table 2.
[0098] Table 2. Particle size, Zeta potential, and fluorescence characteristics of the composite nanodispersion system at different preparation stages:
[0099] According to Table 2 and Figure 2 The results show that the average hydrodynamic particle size, polydispersity index, and zeta potential of the samples at different preparation stages exhibit certain changes.
[0100] Regarding particle size, the average hydrodynamic particle size of the oil-in-water pre-emulsion in Example 1 was 84.7 nm, with a polydispersity index of 0.203. After adding fluorescent carbon dots B from the monk fruit pomace and completing interfacial remodeling, the average hydrodynamic particle size was 114.2 nm, with a polydispersity index of 0.261. After further compounding with inorganic nutrients, the average hydrodynamic particle size of the final product in Example 1 was 126.5 nm, with a polydispersity index of 0.294. These results indicate that during the staged assembly process, the average hydrodynamic particle size of the system gradually increased, while the polydispersity index of the samples at each stage was below 0.3. Considering the changes in average hydrodynamic particle size, it is evident that the dispersion state of the system differs at different preparation stages, and the final product of Example 1 still exhibits a nanoscale dispersion system.
[0101] Regarding the Zeta potential, the Zeta potential of the oil-in-water primary emulsion in Example 1 was -11.6 mV, while the Zeta potential of the emulsion after interfacial remodeling was -28.1 mV. The absolute value of the Zeta potential increased from 11.6 mV to 28.1 mV, indicating that the interfacial electrical characteristics of the system changed after adding the fluorescent carbon point B from the monk fruit pomace and performing pH adjustment and interfacial remodeling. This change is consistent with the participation of the fluorescent carbon point B from the monk fruit pomace in interfacial assembly. Further compounding with inorganic nutrients resulted in a Zeta potential of -17.8 mV for the final product of Example 1, with a lower absolute value compared to the emulsion after interfacial remodeling. This indicates that the addition of inorganic nutrients further altered the interfacial electrical characteristics of the system. Combined with the average hydrodynamic particle size and polydispersity index results of the final product, it demonstrates that the system can still maintain a nanoscale dispersion state after the addition of inorganic nutrients.
[0102] Regarding fluorescence characteristics, the maximum excitation wavelength of the fluorescent carbon dot B in the *Siraitia grosvenorii* pomace was 365 nm, and the maximum emission wavelength was 448 nm. The maximum excitation wavelength of the emulsion after interfacial recombination in Example 1 was 365 nm, and the maximum emission wavelength was 451 nm. The maximum excitation wavelength of the final product in Example 1 remained 365 nm, and the maximum emission wavelength was 454 nm. This indicates that after interfacial recombination and the addition of inorganic nutrients, the system still exhibited fluorescence excitation and emission characteristics similar to those of the fluorescent carbon dot B in the *Siraitia grosvenorii* pomace, while the maximum emission wavelength gradually shifted from 448 nm to 451 nm and 454 nm. This change suggests that the local chemical environment of the fluorescent carbon dot B in the *Siraitia grosvenorii* pomace may have changed during the staged assembly process, while its characteristic fluorescence emission properties were preserved to some extent.
[0103] In summary, the average hydrodynamic particle size, polydispersity index, zeta potential, and fluorescence characteristic parameters changed accordingly with the staged assembly process. These changes are consistent with the process of fluorescent carbon dots B in the pomace of Luo Han Guo participating in interfacial assembly and subsequent inorganic nutrient compounding, which can provide a characterization basis for the formation process and dispersion characteristics of the composite nano-dispersion system.
[0104] Test Example 3: This test case evaluates the dispersion stability and calcium and phosphorus retention of a composite nano-dispersion system under conditions of coexistence of inorganic nutrients by measuring the oil leaching rate, calcium and phosphorus retention rates, and changes in average hydrodynamic particle size and turbidity during storage.
[0105] (1) Sample preparation: Measure 50 mL of the final liquid product obtained from Examples 1 to 6, Comparative Examples 1, 2, 4, and 6, respectively, and place them into stoppered centrifuge tubes. Place the centrifuge tubes in a benchtop high-speed centrifuge, set the speed to 10,000 rpm, and centrifuge for 20 min. After centrifugation, carefully aspirate and collect the upper separated oil phase using a pipette. Calculate the percentage of the separated oil phase mass relative to the theoretical total mass of lipids by weighing, and record this as the centrifugal oil separation rate.
[0106] (2) Centrifugal oil drift rate test: Transfer 200 mL of each sample to a sealed glass bottle and store at 25°C in the dark for 15 days. After the storage period, take 5 mL of the sample, centrifuge at 8000 rpm for 10 min, collect the supernatant, and dilute it 500 times with 2% nitric acid solution. Determine the calcium and phosphorus content in the diluted solution using inductively coupled plasma optical emission spectrometry (ICP-OES), and compare the results with the theoretical input amounts of the corresponding elements to calculate the calcium and phosphorus retention rates.
[0107] (3) Calcium and phosphorus retention rate test Take 200 mL of each of the above test samples, transfer them to sealed glass bottles, and store them at 25℃ in the dark for 15 days. After the storage period, take 5 mL of the sample, centrifuge at 8000 rpm for 10 min, collect the supernatant, and dilute it 500 times with 2% nitric acid solution. Determine the calcium and phosphorus content in the diluted solution using inductively coupled plasma optical emission spectrometry (ICP-OES), and compare it with the theoretical input of the corresponding elements to calculate the calcium and phosphorus retention rates.
[0108] (4) Storage stability test Take the above test samples again and store them at room temperature. Take samples on days 1, 10, 20 and 30. Measure the turbidity of each sample directly using a turbidimeter, in NTU. Take an appropriate amount of sample, dilute it with deionized water, and measure the average hydrodynamic particle size of the system using a dynamic light scattering instrument. Record the changes in average hydrodynamic particle size and turbidity at different storage times.
[0109] The results of centrifugation oil leaching rate, calcium and phosphorus retention rate, and turbidity change after 30 days of storage for each sample are shown in Table 3.
[0110] Table 3. Data on centrifugal oil removal rate, elemental retention rate, and storage stability of the composite nano-dispersion system:
[0111] According to Table 3 and Figure 3 The results show that the centrifugal oil removal rate of Examples 1 to 6 was 0.6% to 1.6%, the calcium retention rate was 90.2% to 96.8%, and the phosphorus retention rate was 91.5% to 96.3%. The turbidity increase from day 1 to day 30 was 8 NTU to 26 NTU. These results indicate that under the test conditions, the composite nano-dispersion systems obtained in each example exhibited a relatively stable dispersion state during centrifugation and storage, and possessed high calcium and phosphorus retention rates.
[0112] Comparative Example 4 did not separately prepare the inorganic salts containing divalent metal ions, nor did it undergo citric acid coordination treatment; instead, all nutrient components were combined at once. After 15 days of storage, the retention rates of calcium and phosphorus were 11.5% and 17.2%, respectively, significantly lower than the 95.4% and 96.3% of Example 1. Simultaneously, the turbidity increase from day 1 to day 30 reached 416 NTU. These results indicate that the nutrient salt preparation and addition method used in Comparative Example 4 is unfavorable for the retention of calcium and phosphorus in the liquid phase, accompanied by a relatively significant change in system turbidity. Considering the decrease in calcium and phosphorus retention rates, it is speculated that this phenomenon may be related to the formation of insoluble substances containing calcium and phosphorus during storage, but their specific composition requires further characterization and determination.
[0113] Comparative Example 6 eliminated the staged high-shear dispersion emulsification, interfacial adsorption assembly, and gradual pH adjustment processes, employing a one-time mixing process. Its centrifugal oil leaching rate was 21.5%, and the turbidity increase from day 1 to day 30 was 208 NTU. Compared to Example 1, Comparative Example 6 exhibited a higher centrifugal oil leaching rate and a larger turbidity change during storage, indicating a certain correlation between different assembly methods and the dispersion stability of the system.
[0114] Comparative Example 1, without the addition of mogroside A, had an oil separation rate of 37.8% after centrifugation and exhibited significant demulsification and stratification during storage. These results indicate that in this test system, the lack of mogroside A significantly reduced the emulsification and dispersion stability of fatty acid component C, suggesting that the addition of mogroside A helps maintain the emulsification and dispersion of fatty acid component C.
[0115] Comparative Example 2, without the addition of Luo Han Guo pomace fluorescent carbon dots B, showed a turbidity increase of 82 NTU from day 1 to day 30, higher than the 11 NTU in Example 1. According to... Figure 3 The results of the average hydrodynamic particle size change shown indicate that the increase in average hydrodynamic particle size with storage time in Comparative Example 2 is also greater than that in Example 1. These results suggest that, under the test conditions, the addition of fluorescent carbon dots B from the monk fruit pomace is correlated with the relatively small changes in particle size and turbidity during system storage. Combined with the zeta potential change results shown in Test Example 2, it is speculated that the participation of fluorescent carbon dots B from the monk fruit pomace in interfacial assembly and alteration of the system's interfacial electrical characteristics may be one of the factors affecting the system's storage stability.
[0116] In summary, under the test conditions, the methods employed in Example 1—specifically, the separate preparation of the inorganic salts containing divalent metal ions, the citric acid coordination treatment, the staged compounding of inorganic nutrients, and the staged interface assembly—correspond to the higher retention rates of calcium and phosphorus elements, the lower rate of oil leaching during centrifugation, and the smaller changes in particle size and turbidity during storage. It should be noted that Comparative Example 4 simultaneously altered the preparation methods of the inorganic salts containing divalent metal ions, the method of adding citric acid, and the method of adding inorganic nutrients. Therefore, its test results reflect the comprehensive impact of these overall changes in conditions, and the corresponding differences should not be attributed to any single factor.
[0117] Test Example 4: This test case evaluates the oxidative stability of α-linolenic acid in a composite nano-dispersion system by measuring the changes in α-linolenic acid retention rate and peroxide value with treatment time in different samples under accelerated oxidation conditions, and compares the combined effects of nitrogen protection and D-α-tocopherol antioxidant protection measures on the oxidative stability of the system.
[0118] (1) Sample preparation: Take 100 mL each of the final product obtained in Example 1, the final product obtained in Comparative Example 5, and fatty acid component C obtained in Preparation Example 3 as test samples, and put them into transparent glass bottles and seal them.
[0119] (2) Accelerated oxidation treatment and sampling: The glass bottles containing the test samples were placed in an accelerated oxidation test in a light incubator at a temperature of 40°C and a light intensity of 2000 lx. Samples were taken on days 0, 5, 10, 15, 20 and 30 of the test.
[0120] For the composite nano-dispersion system samples of Example 1 and Comparative Example 5, 5 mL of sample was taken each time, and a mixed solvent of chloroform and methanol in a volume ratio of 2:1 was added. The mixture was shaken to break the emulsified dispersion and extract the lipids. The lower organic phase was collected, and the organic solvent was removed using a nitrogen blower. For the fatty acid component C, which was in liquid state, the sample was taken directly for subsequent processing.
[0121] (3) α-Linolenic acid retention rate test: Add 0.5 mol / L potassium hydroxide-methanol solution to the lipid sample obtained above, and reflux at 65°C for fatty acid methyl esterification. Extract the treated sample with n-hexane, filter it through a 0.22 μm organic filter membrane, and then inject it into a gas chromatograph equipped with a flame ionization detector (FID) for analysis.
[0122] A quantitative standard curve was established using α-linolenic acid standards. The α-linolenic acid content in the samples at different sampling times was calculated based on the corresponding chromatographic peak areas. The α-linolenic acid retention rate at the corresponding time points was calculated using the α-linolenic acid content of each test sample on day 0 as a benchmark.
[0123] (4) Peroxide value test: Separately, samples from the same batch with different accelerated oxidation times were obtained, and lipid samples were obtained in the same manner as the lipid extraction described above. The peroxide value of the lipid samples was determined by sodium thiosulfate titration.
[0124] The α-linolenic acid retention rate and peroxide value of each test sample under different accelerated oxidation times are shown in Table 4.
[0125] Table 4. Retention rate and peroxide value of free α-linolenic acid in the system at different aging times:
[0126] According to Table 4 and Figure 4 The results show that as the accelerated oxidation time increases, the retention rate of α-linolenic acid in Example 1, Comparative Example 5, and fatty acid component C all show a decreasing trend, while the peroxide value shows an increasing trend. However, the magnitude of the changes varies significantly among different test samples.
[0127] Under accelerated oxidation conditions of 40℃ and 2000 lx, the retention rate of α-linolenic acid in fatty acid component C decreased from 100.0% on day 0 to 38.5% on day 15 and 12.7% on day 30, while the peroxide value increased from 3.6 meq / kg on day 0 to 54.2 meq / kg on day 15 and 93.5 meq / kg on day 30. These results indicate that under the test conditions, the α-linolenic acid content in fatty acid component C significantly decreased with prolonged accelerated oxidation time, accompanied by an increase in the degree of lipid peroxidation.
[0128] Comparative Example 5 did not use nitrogen protection or add D-α-tocopherol when preparing fatty acid component C according to the method of Preparation Example 3, and it also did not use nitrogen protection during the preliminary emulsification process in step (2) of Example 1. Its α-linolenic acid retention rate on day 30 was 51.4%, higher than that of fatty acid component C (12.7%); the corresponding peroxide value was 45.8 meq / kg, lower than that of fatty acid component C (93.5 meq / kg). These results indicate that, under the test conditions, the α-linolenic acid in the composite nano-dispersion system obtained in Comparative Example 5 exhibited a lower degree of oxidation change than that of fatty acid component C alone. This difference corresponds to the formation of an emulsified dispersion state of fatty acid component C in the composite nano-dispersion system, suggesting that the emulsified dispersion state of the system may have a certain influence on the oxidation process of α-linolenic acid.
[0129] In Example 1, nitrogen protection was used during the preparation and initial emulsification of fatty acid component C, and D-α-tocopherol was added for antioxidant protection during the preparation of fatty acid component C. After 30 days of accelerated oxidation, the α-linolenic acid retention rate was 85.2%, higher than that of Comparative Example 5 (51.4%); the corresponding peroxide value was 14.1 meq / kg, lower than that of Comparative Example 5 (45.8 meq / kg). These results indicate that under the test conditions, the α-linolenic acid content in Example 1 showed a smaller decrease, while the increase in lipid peroxide value was relatively small.
[0130] In summary, the formation of the composite nano-dispersion system and the use of nitrogen protection and D-α-tocopherol antioxidant protection during its preparation, corresponding to the high retention rate and low peroxide value of α-linolenic acid under accelerated oxidation conditions, suggest that these factors may collectively affect the oxidative stability of α-linolenic acid in the system. It should be noted that Comparative Example 5 simultaneously eliminated nitrogen protection and the addition of D-α-tocopherol during the preparation of fatty acid component C, as well as nitrogen protection during the initial emulsification process. Therefore, the difference in test results between Example 1 and Comparative Example 5 reflects the combined effect of the changed combination of the above protective measures, and it is inappropriate to attribute the corresponding differences solely to nitrogen protection or D-α-tocopherol.
[0131] Test Example 5: This test case evaluates the compatibility of the composite nano-foliar fertilizer obtained in Example 1 with the Tween-80 alternative system under the test conditions by measuring the relative electrolyte leakage rate, SPAD value and visible leaf damage of the leaves of Luo Han Guo seedlings after different foliar spraying treatments.
[0132] (1) Sample preparation: Healthy monk fruit seedlings with similar plant height, leaf age, and growth were selected as test plants and randomly divided into three groups, each containing 15 seedlings. The final products obtained in Example 1 and Comparative Example 7 were diluted 500 times with deionized water to prepare corresponding foliar spray working solutions; an equal volume of deionized water was used as a blank control.
[0133] Using a pneumatic sprayer, on a clear, windless evening, the above-mentioned working solutions were evenly sprayed onto both sides of the leaves of the corresponding treatment group plants until fine droplets were evenly attached to the leaf surface without significant dripping.
[0134] (2) Relative electrolyte leakage rate test: Samples were taken on day 0 before spraying and on days 1, 3, 5 and 7 after spraying. Using an 8mm diameter punch, leaf discs were taken from the upper leaves of each group of seedlings, avoiding the main vein. Twenty discs were randomly selected from each group.
[0135] After rinsing the leaf discs with deionized water, they were placed in a stoppered test tube containing 20 mL of deionized water. The tubes were then evacuated from the air at room temperature for 10 minutes to remove some of the gas from the interstitial spaces of the leaf tissue. After standing for 2 hours, the initial conductivity was measured using a conductivity meter. The test tubes were then heated in a boiling water bath for 20 minutes, cooled to room temperature, and the total conductivity was measured.
[0136] The relative electrolyte leakage rate is calculated as the ratio of initial conductivity to total conductivity.
[0137] (3) SPAD value test: At the same sampling time point as the relative electrolyte leakage rate, three pre-marked mature leaves from the upper and middle parts of each group of plants were selected. The SPAD values at the upper, middle and lower parts of the same leaf were measured using a portable chlorophyll meter (SPAD-502), and the average value was taken as the SPAD value of the leaf to characterize the change in the relative chlorophyll content of the leaf.
[0138] (4) Statistics of visible leaf damage: On the 7th day after the spraying treatment, the visible leaf damage symptoms of each group of plants were counted. The number of leaves with symptoms such as necrotic spots, yellowing spots or leaf margin drying was recorded, and the incidence of scorch spots was calculated, that is, the percentage of leaves with the above damage symptoms out of the total number of leaves surveyed.
[0139] The relative electrolyte leakage rate, SPAD value, and burn incidence rate on day 7 for each treatment group are shown in Table 5.
[0140] Table 5. Statistical results of physiological indicators and visible leaf damage of Luo Han Guo seedlings under different foliar spraying treatments:
[0141] According to Table 5 and Figure 5 The results show that different foliar spraying treatment groups exhibited certain differences in relative electrolyte leakage rate, SPAD value, and the occurrence of visible leaf damage on day 7.
[0142] Comparative Example 7 used Tween-80 (polysorbate 80) aqueous solution to replace mogroside component A. Its relative electrolyte leakage rate on days 3 and 7 was 28.5% and 34.2%, respectively, both higher than the blank control group's 9.4% and 10.3% and Example 1's 10.7% and 11.4%. The incidence of burn spots on day 7 was 19.3%, while the SPAD value decreased from 39.7 on day 3 to 37.4 on day 7. These results indicate that under the test formulation and spraying conditions, Comparative Example 7 showed relatively high electrolyte leakage and visible leaf damage rates, accompanied by a decrease in SPAD value, suggesting that this substitution system corresponds to lower foliar application compatibility.
[0143] The relative electrolyte leakage rates of Group 1 on days 3 and 7 were 10.7% and 11.4%, respectively, which were close to the corresponding time points of 9.4% and 10.3% in the blank control group; the incidence of burn spots on day 7 was 1.8%. Meanwhile, the SPAD value of Group 1 increased from 46.2 on day 3 to 51.5 on day 7, higher than that of the blank control group and the seven comparative groups during the same period. These results indicate that under the test conditions, the relative electrolyte leakage rate and the incidence of visible leaf damage in the leaves treated with Example 1 remained at a low level, while the SPAD value showed an upward trend.
[0144] Based on the above results, under the test formulation and spraying conditions, the composite nano-dispersion system of Example 1, which uses mogroside component A, exhibits a lower relative electrolyte leakage rate and burn spot incidence rate compared to Comparative Example 7, which uses Tween-80 to replace mogroside component A, while maintaining a higher SPAD value. This indicates that the system of Example 1 has good compatibility for foliar application.
[0145] It should be noted that Comparative Example 7 changed the types of surfactant components. Therefore, the test results mainly reflect the comprehensive differences between the system obtained under the substitution conditions of mogroside component A and Tween-80 in this test formulation and spraying conditions. It is not appropriate to interpret the corresponding differences as general foliar effects of Tween-80 under other concentrations or application conditions.
[0146] Test Example 6: This test case evaluates the effect of the composite nano-foliar fertilizer obtained in Example 1 on the photosynthetic characteristics of Luo Han Guo leaves by measuring the diurnal variation of net photosynthetic rate, stomatal conductance and intercellular CO2 concentration of Luo Han Guo leaves after different foliar spraying treatments, and compares the effect of adding fluorescent carbon dots B to Luo Han Guo pomace on relevant photosynthetic parameters.
[0147] (1) Sample preparation: Healthy monk fruit plants with uniform growth during their growth period were selected as test plants and randomly divided into three groups, with 10 plants in each group. The final product obtained in Example 1, the final product obtained in Comparative Example 2, and a commercially available conventional all-nutrient water-soluble fertilizer were used as test samples. The test samples were diluted 500 times with deionized water to prepare corresponding foliar spray solutions.
[0148] Using a manual sprayer, the above-mentioned foliar spraying solution was evenly sprayed onto both sides of the leaves of the corresponding treatment group plants until the leaf surface was evenly moistened and there was no obvious droplet loss.
[0149] (2) Measurement of diurnal variation of photosynthetic characteristics: Seven days after the spraying treatment, the diurnal variation of photosynthetic characteristics of Luo Han Guo leaves was measured under natural light conditions. A portable photosynthesis meter was used to collect data at 8:00, 10:00, 12:00, 14:00 and 16:00.
[0150] (3) Measurement of photosynthetic parameters: For each measurement, three fully expanded, mature leaves from the middle of each plant in each treatment group, facing the sun without any obstruction, were selected. The leaves were placed in the transparent leaf chamber of a photosynthesis meter, and the airflow rate was set to 500 μmol / s. After the instrument readings stabilized, the net photosynthetic rate, stomatal conductance, and intercellular CO2 concentration were recorded. The average value of the results obtained at the same time point for the same treatment group was taken as the test result for that treatment group.
[0151] The net photosynthetic rate, stomatal conductance, and intercellular CO2 concentration of each treatment group at different time points are shown in Table 6.
[0152] Table 6. Daily variation data of photosynthetic parameters of Luo Han Guo leaves under different foliar spraying treatments:
[0153]
[0154] According to Table 6 and Figure 6 The results show that the net photosynthetic rate, stomatal conductance, and intercellular CO2 concentration of Luo Han Guo leaves all changed with the measurement time after different foliar spraying treatments.
[0155] Regarding net photosynthetic rate, all three treatment groups exhibited a diurnal variation pattern: an increase at 10:00, a decrease at 12:00, a slight increase again at 14:00, and a decrease at 16:00. Specifically, the net photosynthetic rates of Example 1 group at 8:00, 10:00, 12:00, 14:00, and 16:00 were respectively... , , , and At all test time points, the levels were higher than those of the control group 2 and the conventional all-nutrient water-soluble fertilizer group.
[0156] Regarding stomatal conductance, the measured values of Example 1 group at each measurement time point were also higher than those of Comparative Example 2 group and the conventional all-nutrient water-soluble fertilizer group, with the highest value reaching 10:00. Meanwhile, the intercellular CO2 concentration in the Example 1 group was lower than that in the other two treatment groups at all measurement time points. The above results of changes in net photosynthetic rate, stomatal conductance, and intercellular CO2 concentration indicate that under the test conditions, the leaves of *Siraitia grosvenorii* treated in Example 1 exhibited a higher net CO2 assimilation rate, accompanied by corresponding changes in gas exchange parameters.
[0157] The main difference between Comparative Example 2 and Example 1 is that the fluorescent carbon dots B from the monk fruit pomace were not added. The net photosynthetic rates of Comparative Example 2 at each measurement time point were as follows: , , , and The values were all lower than the measured values at the corresponding time points in Example 1; their stomatal conductance also showed similar inter-group differences. Therefore, under the test conditions, the addition of fluorescent carbon dots B to the pomace of *Siraitia grosvenorii* is correlated with the changes in net photosynthetic rate and stomatal conductance of *Siraitia grosvenorii* leaves.
[0158] Based on the results shown in Test Example 2, the fluorescent carbon point B in the monk fruit pomace still exhibited characteristic fluorescence emission around 450 nm after interfacial recombination and inorganic nutrient compounding. This fluorescence characteristic may be related to the changes in photosynthetic parameters observed in the treatment group of Example 1, but the specific mechanism of action cannot be determined solely based on these test results.
[0159] Based on the above results, under the test conditions, the treatment group of Example 1 showed higher net photosynthetic rate and stomatal conductance than the control group 2 and the conventional all-nutrient water-soluble fertilizer group at each measurement time point, and showed a relatively lower intercellular CO2 concentration, indicating that the treatment of Example 1 is related to the changes in photosynthetic characteristics of Luo Han Guo leaves.
[0160] Test Example 7: This test case measures the changes over time in the activities of peroxidase (POD) and phenylalanine ammonia-lyase (PAL) in the leaves of *Siraitia grosvenorii* after different foliar spraying treatments. Combined with the incidence and disease index after anthracnose inoculation, it evaluates the relationship between the treatment in Example 1 and the defense-related physiological responses and subsequent disease resistance phenotypes of *Siraitia grosvenorii* plants, and compares the effect of the addition or absence of fatty acid component C on the above indicators.
[0161] (1) Sample preparation: Shoot fruit plants in the seedling stage with uniform growth and no record of disease infection were selected as test plants and divided into a blank control group, three comparative example groups, and one example group, with 20 plants in each group. The final products obtained in Example 1 and Comparative Example 3 were diluted 500 times with deionized water to prepare corresponding foliar spray working solutions. The working solutions were evenly sprayed onto both sides of the leaves of the corresponding treatment group plants using a metered sprayer, while the blank control group was sprayed with an equal amount of deionized water.
[0162] (2) Assay of defense-related enzyme activity: Functional leaves from the middle part of each group of plants were collected on day 0 before spraying and on days 1, 3, 5, 7 and 10 after spraying. 0.5g of fresh leaf tissue was weighed, added to pre-cooled phosphate buffer, and homogenized. The homogenate was centrifuged at 12000rpm for 15min at 4℃, and the supernatant was collected as crude enzyme extract.
[0163] The absorbance changes of the corresponding reaction systems were measured at wavelengths of 470 nm and 290 nm using a UV-Vis spectrophotometer, and the enzyme activities of peroxidase (POD) and phenylalanine ammonia-lyase (PAL) were calculated.
[0164] (3) Inoculation with pathogens: On the third day after the spraying treatment, the remaining test plants in each group were inoculated with pathogens. Colletotrichum gloeosporioides was used as the test pathogen. A spore suspension with a concentration of 1×106 spores / mL was sprayed evenly onto the plant leaves. The plants were then placed under constant temperature and high humidity conditions of 28℃ and 90% relative humidity for inoculation and culture.
[0165] (4) Evaluation of the incidence rate: On day 14 after pathogen inoculation, the disease incidence of plants in each treatment group was investigated. Disease severity was classified according to the proportion of leaf lesions to the total leaf area, the incidence rate of each treatment group was counted, and the disease index was calculated based on the number of leaves at each disease severity level.
[0166] The POD and PAL activities, as well as the incidence and disease index after pathogen inoculation, of each treatment group on days 3 and 5 are shown in Table 7.
[0167] Table 7. Evaluation results of the activity of defense-related enzymes and disease incidence in Luo Han Guo leaves under different foliar spraying treatments:
[0168] According to Table 7 and Figure 7 The results show that different foliar spraying treatment groups exhibited certain differences in POD activity, PAL activity, and the incidence and disease index after pathogen inoculation.
[0169] On day 3, the POD activities in the blank control group and the three comparative groups were 45.2 U / gFW and 51.8 U / gFW, respectively, and the PAL activities were 12.1 U / gFW and 15.6 U / gFW, respectively. By day 5, both groups showed only relatively limited changes in POD and PAL activities. After pathogen inoculation, the incidence rates in the blank control group and the three comparative groups were 85.6% and 71.4%, respectively, and the disease indexes were 62.3 and 51.8, respectively.
[0170] On day 3, the POD and PAL activities in Group 1 were 96.4 U / gFW and 32.5 U / gFW, respectively, both higher than those in the blank control group and the three comparative groups at the same time point. On day 5, the POD and PAL activities were 115.7 U / gFW and 38.2 U / gFW, respectively. After pathogen inoculation, the incidence rate in Group 1 was 26.2%, and the disease index was 15.4, both lower than those in the blank control group and the three comparative groups.
[0171] It should be noted that pathogen inoculation was carried out on the 3rd day after spraying. Therefore, the POD and PAL activities measured on the 3rd day mainly reflect the activity status of defense-related enzymes corresponding to different foliar treatments before pathogen inoculation. The Example 1 group showed high POD and PAL activities before pathogen inoculation. Combined with the subsequent low incidence and disease index, it suggests that the Example 1 treatment may be related to the pre-enhancement of the defense-related physiological state of the Luo Han Guo plant and may have a certain pre-excitation effect on defense.
[0172] The main difference between Comparative Example 3 and Example 1 is the absence of fatty acid component C. Before pathogen inoculation, the POD and PAL activities in Comparative Example 3 were lower than those in Example 1, and the subsequent disease incidence and disease index were higher. Therefore, under the test conditions, the addition of fatty acid component C is correlated with increased activity of defense-related enzymes and lower disease incidence.
[0173] It should also be noted that the POD and PAL activity measurements on day 5 and thereafter occurred after pathogen inoculation. Therefore, the corresponding enzyme activity changes may be affected by both foliar spraying and pathogen infection. It is not appropriate to attribute all enzyme activity changes after inoculation solely to fatty acid component C or foliar spraying itself.
[0174] In summary, under the test conditions, the treatment group in Example 1 exhibited higher POD and PAL activities before pathogen inoculation and lower morbidity and disease index in subsequent inoculation experiments. These results indicate a certain correlation between the treatment in Example 1 and changes in the defense-related physiological responses and disease resistance phenotypes of *Siraitia grosvenorii* plants.
[0175] Although embodiments of the invention have been shown and described, it will be understood by those skilled in the art that various changes, modifications, substitutions and alterations can be made to these embodiments without departing from the principles and spirit of the invention, the scope of which is defined by the appended claims and their equivalents.
Claims
1. A broad-spectrum, all-purpose nano-foliar fertilizer, characterized in that, It is prepared from raw materials containing the following proportions: Monk fruit glycoside component A: 400-600 mL; Fatty acid component C: 2.0–5.0 g; Luo Han Guo pomace fluorescent carbon dots B: 150-350 mL; Inorganic nutrient system: 7.0–8.0g; Anhydrous citric acid: 2.26–2.89 g; And replenish to 1000 mL of deionized water; The above-mentioned raw materials are mixed and the pH of the final product is adjusted to 6.0-7.0 using a pH adjuster. The broad-spectrum all-effect nano-foliar fertilizer is constructed into a stable nano-multiphase system by multi-component interfacial recombination. Among them, the mogroside component A acts as an amphiphilic skeleton to encapsulate the fatty acid component C to form an oil-in-water type colostrum, so as to provide plant foliar compatibility. The anhydrous citric acid forms a pre-coordination structure with the divalent metal ions in the inorganic nutrient system to prevent co-precipitation of inorganic salts in high-salt and near-neutral environments. The fluorescent carbon dots B of mogroside pomace are cross-linked and adsorbed at the interface by the oxygen-containing functional groups on the surface of the emulsion interface components and the coordinated metal ions under the induction of the pH adjuster, so as to provide steric stabilization and light energy conversion function under natural light excitation.
2. The broad-spectrum, all-effect nano-foliar fertilizer according to claim 1, characterized in that, The inorganic nutrient system consists of inorganic salt components containing divalent metal ions and other nutrient components; The inorganic salt components containing divalent metal ions include calcium nitrate tetrahydrate, magnesium sulfate heptahydrate, zinc sulfate heptahydrate, manganese sulfate monohydrate, copper sulfate pentahydrate, and cobalt chloride hexahydrate; the remaining nutrient components include ammonium nitrate, potassium nitrate, potassium dihydrogen phosphate, potassium iodide, boric acid, and sodium molybdate dihydrate. The ratio of the amount of anhydrous citric acid used to the total number of moles of divalent metal ions in the inorganic nutrient system is 1.0:1 to 1.2:
1.
3. The broad-spectrum, all-effect nano-foliar fertilizer according to claim 1, characterized in that, The mogroside component A is an extract rich in natural mogrosides obtained from mogroside pomace after low-temperature water extraction and solid-liquid separation; the fluorescent carbon dots B from the mogroside pomace are carbon dot dispersions generated by high-pressure hydrothermal reaction using the remaining solid residue after the above low-temperature water extraction and separation as a carbon source.
4. The broad-spectrum, all-effect nano-foliar fertilizer according to claim 1, characterized in that, The fatty acid component C is an active component rich in free α-linolenic acid, obtained by isothermal enzymatic hydrolysis of perilla seed meal lipids by Candida lipase under nitrogen and antioxidant protection.
5. A method for preparing a broad-spectrum, all-effect nano-foliar fertilizer, used to prepare the broad-spectrum, all-effect nano-foliar fertilizer as described in any one of claims 1-4, characterized in that, Includes the following steps: S1. Solution preparation: Dissolve the inorganic salt component containing divalent metal ions in deionized water separately, add an appropriate amount of anhydrous citric acid, and stir to prepare a divalent metal ion citric acid complex solution; dissolve the remaining nutrient components in deionized water to prepare the remaining nutrient solutions. S2. Preliminary emulsification: Under inert gas protection and heating conditions, fatty acid component C is added dropwise to mogroside component A at a uniform rate, and oil-in-water type primary emulsion is obtained through high shear dispersion emulsification treatment; S3, Interfacial Adsorption Assembly and pH-Induced Recombination: Reduce the stirring speed and pump Luo Han Guo fruit residue fluorescent carbon dots B into the water-in-oil type primary emulsion obtained in S2; then, under continuous stirring, simultaneously add the divalent metal ion citric acid complex solution and pH adjuster prepared in S1, control the pH value of the system to slowly rise to the target endpoint of 6.0-7.0 and maintain constant temperature stirring to complete the interfacial structure recombination. S4. Compounding and preparation of final product: Pump the remaining nutrient salt solution obtained in S1 into the system after S3 recombination, mix evenly, cool down, add deionized water to the rated volume, and then discharge to obtain the final product.
6. The method for preparing a broad-spectrum, all-effect nano-foliar fertilizer according to claim 5, characterized in that, In step S2, the operating parameters for the preliminary emulsification are as follows: nitrogen gas is introduced for protection, and the system temperature is maintained at 40℃~45℃; the rotation speed of the high shear dispersion emulsifier is set to 1500~2000 rpm; the dripping rate of the fatty acid component C is 2~3 mL / min, and emulsification is continued for 30~45 min after the dripping is completed.
7. The preparation method of the broad-spectrum all-effect nano-foliar fertilizer according to claim 5, characterized in that, In step S3, the pumping flow rate of the fluorescent carbon dots B in the monk fruit pomace is 5-10 mL / min; the pH adjuster is a 10wt%-12wt% potassium hydroxide aqueous solution; the dropping rate of the pH adjuster is controlled so that the pH value of the system rises slowly at an average rate of 0.1-0.15 pH units / min until the target recombination endpoint of pH value of 6.0-7.0 is reached, and the system is stirred at a constant temperature for 30-45 min under this pH condition.
8. The preparation method of the broad-spectrum all-effect nano-foliar fertilizer according to claim 5, characterized in that, In step S2, the mogroside component A is prepared through the following pretreatment steps: Mix the monk fruit residue with deionized water at a mass ratio of 1:10 to 1:15, control the extraction temperature at 50℃ to 60℃, and the extraction time at 2.0h to 3.0h. Filter the mixture through a 200-mesh filter to separate the solid and liquid components. Collect the extract to obtain monk fruit glycoside component A. The separated solid residue is used for later use.
9. The preparation method of the broad-spectrum all-effect nano-foliar fertilizer according to claim 5, characterized in that, In step S3, the fluorescent carbon dots B from the monk fruit pomace are prepared through the following pretreatment steps: The solid residue obtained by separation according to claim 8 is placed in a high-pressure hydrothermal reactor, deionized water is added to control the solid-liquid mass ratio to be 1:5 to 1:10, the hydrothermal reaction temperature is set to 180℃ to 220℃, and the reaction is kept at this temperature for 8h to 10h. After naturally cooling to room temperature, the insoluble solids are filtered out, and the obtained filtrate is the fluorescent carbon point B of the monk fruit residue.
10. The preparation method of the broad-spectrum all-effect nano-foliar fertilizer according to claim 5, characterized in that, In step S2, the fatty acid component C is prepared through the following pretreatment steps: The lipids extracted from perilla seed meal were mixed with deionized water at a mass ratio of 1:3 to 1:5, and Candida lipase was added. The mixture was then enzymatically hydrolyzed at a constant temperature of 40℃ to 45℃ for 2.0 h to 4.0 h. Nitrogen gas was continuously introduced during the enzymatic hydrolysis, and D-α-tocopherol was added at 0.1 wt% to 0.3 wt% of the lipid mass. After the enzymatic hydrolysis was completed, the temperature was raised to 85℃ to inactivate the enzyme. The mixture was then centrifuged, and the upper lipid phase was collected, which was the fatty acid component C.